Optimization of E-Government Through Information Technology Management - Indiati Indiati; Suljatmiko Suljatmiko; Cecep Wahyu Hoerudin; Ufa Anita Afrilia; Sri Wulan Windu Ratih (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
E-Government has become the main driver in the transformation of public services through the management of Information Technology (IT). In this context, it is important to understand the positive impact produced by IT, as well as identify obstacles and effective management strategies to optimize E-Government. This research aims to investigate developments and challenges related to E-Government through IT management, as well as to identify effective strategies for dealing with these dynamics. This research uses a descriptive qualitative approach with data analysis from various research sources and previous studies that are relevant to the research topic. The results of this research provide in-depth insight into the role of IT in E-Government, the challenges that need to be overcome, as well as effective strategies for managing government IT. In the future, collaboration between the public and private sectors, integration of advanced technology, and response to cyber security threats will be the key to the success of an E-Government that is more efficient and relevant to society's demands. This research provides a valuable basis for improvement and innovation in government management in the digital era.